O exercício profissional dos Assistentes Sociais nos CREAS da região Oeste do Paraná: gênese a atualidade - Santos, Sonia dos (2020)
The present dissertation work has as its central theme the Social Assistance that admits given particularity, having as object of research the professional practice of social workers in CREAS in the western region of Paraná. We intend to respond as a general objective: to apprehend, understand and analyze under what circumstances Social Assistants professionals, when dealing with violation of rights, are likewise placed in a situation of violation of rights, in their professional practice in CREAS in the West Region of Paraná. During the research, in which came to light this dissertation, we followed the direction that answered the following problem: considering that the social workers, linked in their professional exercises to CREAS, act to answer the demands related to violation of rights, to what extent the professional themselves are also placed in a situation of violation of rights, as their conditions of professional practice are precarious. To answer the main question, the research process was based on an exploratory study, using qualitative and quantitative content existing in three moments: in bibliographic research, using Marxian references and the Marxist tradition; in Social Assitance regulations; in field research, conducting interviews with professionals working at CREAS in western Paraná. The research corroborates our understanding of CREAS as a field for the professional practice of Social Work. However, considerations are elaborated about the precarious working conditions in the area of violation of rights, where the rights of social workers are violated.